Porterandia postarii - Tsen, S.; Hor, C.S.; Damit, A.; Khoo, E.; Matusin, D.; Colin Ruzelion Maycock; Mohd Yusof; Nur Adillah, M.Y.; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Porterandia postarii is a tree endemic to Sabah, Malaysia. It is found in ultramafic forests across the state. There are no major threats to this species, as all localities are within totally protected areas. Hence, it is assessed as Least Concern. Poterandia postarii is endemic to Sabah, Malaysia. It is found in ultramafic forests across the state.